Formulation and development of ‘Berangan’ peel jelly and its antioxidant properties. - Noor Azwani Mohd Rasidek (2014)
This thesis presents the formulation and development of ‘Berangan’ peels to form dessert jelly product with its antioxidant properties. The jelly formulation using ‘Berangan’ peel powder (BPP), formulated without additive any pectin sources. The ‘Berangan’ peel jelly (BPJ) designated under two levels full of factorial which generated of sugar amount (19.00 to 19.30 g) and citric acid (0.207 to 0.209 g) and responded to its total soluable solid, TSS (63.8 to 80.4ºBrix) and pH (3.21 to 3.38) for each BPJ formulation. The targeted response at pH 3.3, TSS 72ºBrix in response optimizer has verified the local solution with 0.846 of composite desirability. Meanwhile, the predicted responses of pH and TSS denotes to desirability at 0.747 and 0.959 respectively. Both predicted response indicates a relatively good consistency of BPJ. The predictive flow model resulted in a reasonably poor fitting to Power Law with R2 is 0.991 to 0.994 and flow behavior index, n is 0.224 to 0.779. The Herschel-Bulkey presented n values at 0.95 to 4.153 which indicated shear thinning and shear thickening behavior in nature. Otherwise, the Casson model, they comprised of R2 values at 0.999 to 1.000.There is almost no yield stress observed in BPJ at low TSS, while at high TSS, the value of yield stress is 0.2. Thus, it concludes that Casson model fits well at higher concentration. The frequency sweep studies at 25ºC which the G’ considered as an indicator of gel rigidity, with BPJ have a low G' value, that derived from determining the texture and quality of jelly itself as a naturally pectin weak behavior.